1991
DOI: 10.1007/bf00408360
|View full text |Cite
|
Sign up to set email alerts
|

No association between islet cell antibodies and coxsackie B, mumps, rubella and cytomegalovirus antibodies in non-diabetic individuals aged 7?19 years

Abstract: Summary. Viral antibodies were tested in a cohort of 44 isletcell antibody-positive individuals age 7-19 years, and 44 of their islet cell antibody-negative age and sex-matched classmates selected from a population study of 4208 pupils who had been screened for islet cell antibodies. Anti-coxsackie B1-5 IgM responses were detected in 14 of 44 (32 %) of the islet cell antibody-positive subjects and in 7 of 44 (16 % ) control subjects. This difference did not reach the level of statistical significance. None of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1992
1992
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…One report suggested that ICA occur with a higher frequency in those diabetic patients with moderate to high CB4 antibody titres [88]. With mumps infection the ICA induced are not always associated with diabetes [89].…”
Section: Autoimmunity and Virusesmentioning
confidence: 99%
“…One report suggested that ICA occur with a higher frequency in those diabetic patients with moderate to high CB4 antibody titres [88]. With mumps infection the ICA induced are not always associated with diabetes [89].…”
Section: Autoimmunity and Virusesmentioning
confidence: 99%
“…Separate aspects of this study have been published recently [12,13]. Here we addressed the question of whether the detection of antibodies to the 64K protein or other Type 1 diabetes specific autoantibodies can be correlated with genetic high risk markers and impaired Beta-cell function.…”
mentioning
confidence: 99%
“…The enzyme glutamic acid decarboxylase (GAD65) has recently been recognized as a major autoantigen in insulindependent diabetes mellitus [1][2][3]. A T-cell response corresponding to carboxyterminal epitopes of the GAD-molecule was found to characterize the pre-diabetic phase in the NOD mouse model [4,5].…”
Section: Introductionmentioning
confidence: 99%